Universal Vouchers and Racial and Ethnic Segregation - Brunner, Eric J.; Imazeki, Jennifer; Ross, Stephen L. (The Review of Economics and Statistics, 2010)
We use data on vote outcomes from a universal voucher initiative to examine whether white households with children in public schools will use vouchers to leave predominantly nonwhite schools, thereby contributing to more racially and ethnically segregated schools. We find that white households are more likely to support vouchers when their children attend schools with larger concentrations of nonwhite schoolchildren, an effect that is absent for nonwhite households and households without children. This result may be driven less by race or ethnicity and more by other characteristics, such as student performance, that are correlated with race or ethnicity.